Whiplash injury: New approaches of functional neuroimaging - Otte, Andreas (Springer Berlin Heidelberg, 2012)
In the past two decades much has been published on whiplash injury, yet both the confusion regarding the condition and the medicolegal discussion surrounding it have increased. In this scenario, a guide to recent and current international research in the field is more necessary than ever. Especially functional imaging methods - such as single-photon emission tomography, positron emission tomography, functional MRI, and hybrid techniques - have demonstrated a variety of significant brain alterations. This book accordingly offers a critical approach to the challenging interpretation of the new research data obtained using functional neuroimaging in whiplash injury. It covers all aspects, including the imaging tools themselves and the different methods of image analysis. Whiplash Injury: New Methods of Functional Neuroimaging will hopefully help patients, their relatives and friends, physicians, and others to understand this condition as a disease.